Islamic Religious Education in the Digital Era through Multidisciplinary Perspectives of Pedagogy Technology and Sociology - Muhammad Eissawy Abu El Yazid; Ahmad Faizal Syahrul Azmi; Ahmad Fauzan Akbar (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
This study aims to analyze Islamic religious education in the digital era using multidisciplinary perspectives including pedagogy, educational technology, and sociology. The research employs a library research method by examining books, journal articles, and relevant academic sources. The findings indicate that digital technology reshapes learning models, teacher roles, and student engagement in Islamic education. Multidisciplinary integration strengthens critical thinking, contextual understanding, and adaptive religious learning suited to contemporary digital society